Stretch-shortening cycle utilization in female and male soccer players: A systematic review - Santos, S. C. R.; Oliveira, A. R.; Costa, R. A.; Nascimento, K. S. B.; Alvares, P. D.; Medeiros, F. B.; Assumpção, C. O.; Ramos, G. P.; Banja, T.; Veneroso, C. E.; Claudino, J. G.; Cabido, C. E. T. (The Journal of Strength and Conditioning Research, 2024)
The stretch-shortening cycle (SSC) enhances strength and power in soccer players. However, little consistent information is found on expected SSC utilization in soccer players. The aim of the present study was to provide information on SSC utilization in soccer players of different sexes, ages, and competitive levels through the calculation of the percent of prestretch augmentation (PPA ((CMJ - SJ)/SJ × 100)). A systematic review was performed of studies involving soccer players. After screening 3,921 studies, 214 assessing a total of 11,941 players were considered eligible. Twenty studies involved females (747 subjects), 16 of which involved professionals (380 players), and 7 of which involved nonprofessionals (367 players). One hundred ninety-seven studies involved males (11,194 subjects), 56 of which involved professionals (2,508 players), 16 involved semiprofessionals (698 players), and 135 involved young athletes [67 involved postpubertal youths (2,439 players) and 85 involved youths (5,549 players)]. Prestretch augmentation was 9.35% (95% CI: 6.33-12.38%) for professional and 5.73% (95% CI: 3.06-8.40%) for nonprofessional female players. For males, PPA was 6.16% (95% CI: 5.03-7.29%) for professional players, 8.55% (95% CI: 5.76-11.33%) for semiprofessionals, 6.64% (95% CI: 5.76-7.53%) for postpubertal youths, and 7.00% (95% CI: 6.11-7.90%) for youths. Stretch-shortening cycle utilization measured based on PPA in the sample studied ranged from 3.06 to 12.38%. These values could serve as reference to indicate the appropriate use of SSC among soccer players according to competitive level and sex, which could help coaches and physical trainers develop appropriate training programs.